Co-infection of a hypovirulent isolate of Sclerotinia sclerotiorum with a new botybirnavirus and a strain of a mitovirus - Ran, Hongchang (Virol J, 2016)
BACKGROUND: Sclerotinia sclerotiorum, a notorious plant fungal pathogen, causes yield loss of many crops and vegetables, and is a natural host of a diverse viruses with positive-sense RNA (+ssRNA), negative-sense RNA (−ssRNA), double-stranded RNA (dsRNA), or DNA genomes. Mixed-infection with multiple related or unrelated mycoviruses is a common phenomenon in S. sclerotiorum. However, a single strain co-infected with dsRNA and + ssRNA viruses has not been reported in S. sclerotiorum. RESULTS: We report two unrelated viruses, Sclerotinia sclerotiorum botybirnavirus 2 (SsBRV2) with a bipartite dsRNA genome and Sclerotinia sclerotiorum mitovirus 4 (SsMV4/AH16) with a + ssRNA genome, which were originally detected in a single hypovirulent strain AH16 of S. sclerotiorum. SsMV4/AH16 has a typical genome of mitovirus and is a strain of mitovirus SsMV4. The genome of SsBRV2 consists of two separated dsRNA segments. The large dsRNA segment is 6159 bp in length and only has a single open reading frame (ORF) encoding a putative 1868-aa polyprotein with a conserved RNA dependent RNA polymerase (RdRp) domain. The small dsRNA segment is 5872 bp in length and encodes a putative 1778-aa protein. Phylogenetic analysis using RdRp conserved domain sequences revealed that SsBRV2 is phylogenetically related to the previously reported three bipartite viruses SsBRV1, Botrytis porri RNA virus 1 (BpRV1), and soybean leaf-associated botybirnavirus 1 (SlaBRV1). Electron microscopy demonstrated that SsBRV2 forms rigid spherical virions with a diameter of approximately 40 nm in infected mycelia. The virion of SsBRV2 was successfully introduced into a virus-free strain, which provides conclusive evidence that SsBRV2 confers hypovirulence on phytopathogenic fungus S. sclerotiorum. CONCLUSIONS: A bisegmented dsRNA virus (SsBRV2/AH16) and a nonsegmented + ssRNA virus (SsMV4/AH16) were characterized in a hypovirulent strain AH16 of S. sclerotiorum. SsMV4/AH16 is a strain of a reported mitovirus, whereas SsBRV2 is a new botybirnavirus. SsBRV2 is the causal agent of hypovirulence on S. sclerotiorum. Our findings supplied a first evidence that a single S. sclerotiorum strain is co-infected by dsRNA and + ssRNA mycoviruses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12985-016-0550-2) contains supplementary material, which is available to authorized users.